2021
DOI: 10.5306/wjco.v12.i11.1047
|View full text |Cite
|
Sign up to set email alerts
|

Pathological response to neoadjuvant therapy with chemotherapy vs chemoradiotherapy in stage III NSCLC. Contribution of IASLC recommendations

Abstract: BACKGROUND Neoadjuvant treatment (NT) with chemotherapy (Ch) is a standard option for resectable stage III (N2) NSCLC. Several studies have suggested benefits with the addition of radiotherapy (RT) to NT Ch. The International Association for the Study of Lung Cancer (IASLC) published recommendations for the pathological response (PHR) of NSCLC resection specimens after NT. AIM To contribute to the IASLC recommendations showing our results of PHR to NT Ch v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…6 Huang et al reported a better pathological response in neoadjuvant immunotherapy compared with neoadjuvant chemotherapy in stage III (N2) NSCLC, 18 with a MPR of 12.8% and a pCR of 2.6% in the neoadjuvant chemotherapy group. In terms of neoadjuvant chemoradiotherapy, a retrospective multi-institutional Phase II study compared the pathological responses of neoadjuvant chemotherapy or chemoradiotherapy in stage III (N2) NSCLC, 28 which reported a MPR of 54.5% in the tumor and 80% downstaging in the neoadjuvant chemoradiotherapy group, and 9.5% and 33.3% in the neoadjuvant chemotherapy group, respectively. Neoadjuvant immunotherapy or chemoradiotherapy appeared to obtain better pathological responses than neoadjuvant chemotherapy, and more well-designed head-to-head studies should be conducted comparing neoadjuvant immunotherapy and chemoradiotherapy with robust results.…”
Section: Discussionmentioning
confidence: 99%
“…6 Huang et al reported a better pathological response in neoadjuvant immunotherapy compared with neoadjuvant chemotherapy in stage III (N2) NSCLC, 18 with a MPR of 12.8% and a pCR of 2.6% in the neoadjuvant chemotherapy group. In terms of neoadjuvant chemoradiotherapy, a retrospective multi-institutional Phase II study compared the pathological responses of neoadjuvant chemotherapy or chemoradiotherapy in stage III (N2) NSCLC, 28 which reported a MPR of 54.5% in the tumor and 80% downstaging in the neoadjuvant chemoradiotherapy group, and 9.5% and 33.3% in the neoadjuvant chemotherapy group, respectively. Neoadjuvant immunotherapy or chemoradiotherapy appeared to obtain better pathological responses than neoadjuvant chemotherapy, and more well-designed head-to-head studies should be conducted comparing neoadjuvant immunotherapy and chemoradiotherapy with robust results.…”
Section: Discussionmentioning
confidence: 99%